Influence of substances from Chlorella on the human body - Chvaliuk, H.V.; Hrubinko, V.V. (Problems of Environmental Biotechnology, 2023)
Chlorella is a green microalgae that is a superfood (concentrate of useful substances that exceed the indicators of average statistical products). Chlorella cells contain such a large number of different nutrients and biologically active compounds that there can be no doubt about the positive effect of food additives based on it.